Rattus nitidus - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
673. White-footed Indochinese Rat Rattus nitidus French: Rat soyeux / German: Himalaya-Ratte / Spanish: Rata de Indochina de pies blancos Other common names: Himalayan Field Rat Taxonomy. Mus nitidus Hodgson, 1845, “central regions of Nepal.” Rattus nitidus is in the R. norvegicus species group;it is morphologically similar to R. nor vegicus and its sister species. Monotypic. Distribution. N & NE India, E Nepal, extreme W & E Bhutan, W, N & E Myanmar, C, SC & SE China (including Hainan I), N Thailand, Laos, Vietnam (including offshore Cat Ba I), and probably E Bangladesh. Introduced to the Philippines (Luzon I), C Sulawesi, Seram I, NW New Guinea, and Palau, although it may be more widely introduced. Descriptive notes. Head—body 148-180 mm, tail 135-206 mm, ear 21 mm, hindfoot 32-36 mm; weight 110-140 g. Males (136 g) are heavier on average and have longer hindfeet than females (114 g); northern populations also seem to be larger than southern populations. The White-footed Indochinese Rat is medium-sized and very similar to the Brown Rat (R. norvegicus), with similarly robust body and broad nose (most easily distinguished by its proportionally shorter hindfeet and its overall smaller body). Pelage is soft, short, and thick. Dorsum generally consists of dark grayish row with mix of pale brown and black-tipped hairs, although shades of brown vary: sides are somewhat lighter. Venter is duller grayish brown and not sharply demarcated from dorsal pelage. Feet are long and white throughout, with pearly luster dorsally. Ears are rounded and lighter brown; vibrissae are long and stiff. Tail is 91-105% of head-body length and usually unicolored, brown orslightly paler ventrally. Skull has long rostrum and robust structure, similar to that of the Brown Rat. The blood fluke Schistosoma japonicum and various trematodes, cestodes, nematodes, ticks, mites, fleas, and lice have been recorded from the Whitefooted Indochinese Rat. There are six pairs of mammae: three axillary and three inguinal. Chromosomal ...